EFFECT OF SATTVIC DIET ON SYSTOLIC BLOOD PRESSURE AND DIASTOLIC BLOOD PRESSURE WHICH INFLUNCE ON YOGIC PRACTICES AMONG COLLEGE STUDENTS - Itoo, Javead Ahmed; Kumar, A. Suman; Vairavasundaram, C. (International Journal of Psychosocial Rehabilitation, 2020)
The present random group experimental study was designed to find out the effect of Sattvic Diet on Systolic blood pressure and diastolic blood pressure on yogic practices among College Students. It was hypothesized that there would be significant difference due yogic practices with Sattvic Diet than the control group on Systolic blood pressure and diastolic blood pressure among College Students. To achieve the purpose of the study, thirty (30) College Students residing in Jammu and Kashmir age between 18 to 22 years were selected randomly two groups, namely a experimental group and control group of fifteen (15) subjects each. Training period of this study was twelve weeks. Experimental group underwent yoga practices with Sattvic Diet for twelve (12) weeks, six days a week for a maximum of one hour in the morning. The control group was kept in active rest. The pre test and post test were conducted before and after the training for all two groups. To analyses the data (ANCOVA) was used. The test of significance was fixed as 0.05 level of confidence. It was concluded that there was significant decreased in yogic practices with Sattvic Diet than the control group on Systolic blood pressure and diastolic blood pressure among College Students.